2001
DOI: 10.1002/ptr.686
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic coumarins and lignans from extracts of the northern prickly ash (Zanthoxylum americanum)

Abstract: Four pyranocoumarins; dipetaline, alloxanthoxyletin, xanthoxyletin and xanthyletin; and two lignans; sesamin and asarinin were isolated from the northern prickly ash, Zanthoxylum americanum. To varying degrees, all inhibited the incorporation of tritiated thymidine into human leukaemia (HL-60) cells. Dipetaline was the most active with an IC(50) of 0.68 ppm, followed by alloxanthoxyletin (1.31 ppm), sesamin (2.71 ppm), asarinin (4.12 ppm), xanthoxyletin (3.48 ppm) and xanthylletin (3.84 ppm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 9 publications
2
37
0
1
Order By: Relevance
“…Here we provide evidence showing that ())-sesamin-induced G 1 phase arrest is triggered by DNA DSBs. Interestingly, several coumarin and lignan derivatives including sesamin and asarinin inhibited DNA synthesis in human leukemia HL-60 cells, (42) both of which are potent inhibitors of Lon protease ( (44) and this work). Double-strand breaks are the most cytotoxic DNA lesions and activate the DNA damage response, which determine cell fate such as cell cycle arrest, repair, or apoptosis.…”
Section: Discussionmentioning
confidence: 64%
“…Here we provide evidence showing that ())-sesamin-induced G 1 phase arrest is triggered by DNA DSBs. Interestingly, several coumarin and lignan derivatives including sesamin and asarinin inhibited DNA synthesis in human leukemia HL-60 cells, (42) both of which are potent inhibitors of Lon protease ( (44) and this work). Double-strand breaks are the most cytotoxic DNA lesions and activate the DNA damage response, which determine cell fate such as cell cycle arrest, repair, or apoptosis.…”
Section: Discussionmentioning
confidence: 64%
“…Ju and co-workers reported that 5 inhibited the incorporation of tritiated thymidine into human leukemia (HL-60) cells, which means that it inhibited DNA synthesis. They indicated that the 50% inhibition concentration (IC 50 ) of 5 is 3.48 ppm (15.28 lM) [21], and this was one of a range of concentrations we examined. Although the cell line was certainly different, it is possible that xanthoxyletin could exert a certain action on the gene constructional system, and it is suggested that this could have caused the suppression of iNOS expression.…”
Section: Resultsmentioning
confidence: 99%
“…Islam et al (2001) verified that etheric extracts from the bark of Z. rhesta are toxic to Artemia salina which, on the other hand, does not suffer toxic action from chlorophormic extracts of Z. budrunga; Ju et al (2001) showed that Z. americanum presented substances, as dipetaline, alloxanthoxyletin e sesamin, that inhibit the DNA synthesis in HL-60 cells; Rodrigues et al (1998) reported the hexane extracts of Z. naranjillo induced alterations in albumin and alkaline phosphatase levels in mice, without liver or biliary alterations, which suggests a possible absence of clinical toxicity. From these studies, it is possible to confirm several potential therapeutical uses of plants from the genus Zanthoxylum.…”
Section: Introductionmentioning
confidence: 94%